1998
DOI: 10.1046/j.1469-8137.1998.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Host and cell type affect the mode of degradation by Meripilus giganteus

Abstract: Wood degradation by the white-rot basidiomycete Meripilus giganteus (Pers. : Pers.) Karst. was studied in naturally infected and artificially inoculated wood of beech (Fagus sylvatica L.) and large-leaved lime (Tilia platyphyllos Scop.). Semi-thin sections revealed that the secondary walls of most fibres contained internal cavities. Three distinct types of cavity formation, which differed not only between hosts, but also between cell type and location in the annual ring, were identified.Within discolour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 27 publications
1
38
0
1
Order By: Relevance
“…The interesting choice of fungi provides evidence to explain the mechanisms by which the fungi breach the reaction-zone barrier. Recent work has shown that the cavity-forming soft rot decay process is not exclusive to members of the lower ascomycetes and deuteromycetes, but can be demonstrated in some wood-decay basidiomycetes (Nilsson & Daniel, 1988;Daniel et al, 1992;Schwarze et al, 1995;Worrall et al, 1997;Schwarze & Fink, 1997, 1998. The fungi chosen for this study also demonstrated soft rot capability as a means of bypassing the blocked cell lumina of the reaction zones.…”
Section: Reaction-zone Penetrationmentioning
confidence: 80%
See 1 more Smart Citation
“…The interesting choice of fungi provides evidence to explain the mechanisms by which the fungi breach the reaction-zone barrier. Recent work has shown that the cavity-forming soft rot decay process is not exclusive to members of the lower ascomycetes and deuteromycetes, but can be demonstrated in some wood-decay basidiomycetes (Nilsson & Daniel, 1988;Daniel et al, 1992;Schwarze et al, 1995;Worrall et al, 1997;Schwarze & Fink, 1997, 1998. The fungi chosen for this study also demonstrated soft rot capability as a means of bypassing the blocked cell lumina of the reaction zones.…”
Section: Reaction-zone Penetrationmentioning
confidence: 80%
“…Material deposited by the host as a defence mechanism and barrier to invasion is therefore viewed as a form of containment against the fungal pathogen. The fact that reaction zones can be breached by fungi (Schwarze & Fink, 1997, 1998, and the mechanism by which this occurs, have particular relevance in understanding the invasive potential of decay fungi in standing trees.…”
Section: Reaction-zone Penetrationmentioning
confidence: 99%
“…The most remarkable anatomical effect is separation of fibres by dissolution of the middle lamellae. In simultaneous rot, lignin and structural polysaccharides are attacked in more or less similar fashion (Worrall et al 1997;Schwarze and Fink 1998). Wood degradation by I. hispidus in Ailanthus has both a white and soft rot pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Based on degradation pattern, infection is usually separated into three types: white rot, brown rot and soft rot (Liese 1970;Blanchette 1991;Eaton and Halle 1993;Schwarze and Fink 1998). In white rot, all cell constituents are degraded and broadly classified into: (a) selective delignification and (b) simultaneous rot.…”
Section: Discussionmentioning
confidence: 99%
“…These were fixed in a 2% (w/w) glutaraldehyde buffered at pH 7.2-7.4, dehydrated with acetone and embedded in a methacrylate medium (Schwarze and Fink 1998). They were then sectioned at approximately 2 and 4 mm with a rotary microtome (Leica ᮋ 2040 Supercut) fitted with a diamond knife.…”
Section: Light Microscopymentioning
confidence: 99%